Pengembangan Pembelajaran Sepak Takraw Berbasis Blended Learning untuk Mahasiswa Prodi PJKR FKIP UNTAD - Tesa Alex Suhendra; Didik Purwanto (Universitas Muhammadiyah Jember, 2022)
The results of this study will produce a product development in the form of books, interactive multimedia and online learning. While the learning components that are carried out in this research are face to face, offline learning that uses studio 8 autoplay application which covers various learning materials, while for online learning using social media, namely google classroom. The results of the research that has been carried out by involving as many as 39 research samples and the results of product trials are: the criteria for product attractiveness are obtained by a percentage of 92.30%, the criteria for product clarity obtained a percentage of 90.06%, the criteria for product convenience obtained a percentage of 91.98%, criteria for effectiveness the product obtained a percentage of 91.45%. The average overall yield of the percentage is 91.59%. This criterion has fulfilled the feasibility, so that the product development of blended learning based sepak takraw courses is considered very valid, on the results of the percentage of the large group test the percentage results decrease compared to the percentage of the small group test of 2.02%, but this does not affect the criteria product validity (very valid) in accordance with the percentage criteria table of data processing results that with the results of 75.01%-100.00% included in the category of very valid and usable.